2013
DOI: 10.1021/tx400050r
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Potencies and Relative Toxicities of γ-Coniceine and N-Methylconiine Enantiomers

Abstract: γ-Coniceine, coniine, and N-methylconiine are toxic alkaloids present in poison hemlock (Conium maculatum). We previously reported the comparison of the relative potencies of (+)- and (-)-coniine enantiomers. In this study, we synthesized γ-coniceine and the enantiomers of N-methylconiine and determined the biological activity of γ-coniceine and each of the N-methylconiine enantiomers in vitro and in vivo. The relative potencies of these piperidine alkaloids on cells expressing human fetal muscle-type nicotini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…[50,60] Lethal doses (LD 50 ) in mice for selected alkaloids are presented in Table 2. [61] The differences in the chemical structures including stereochemistry impart differ-ences in toxicity/potency. For example, (-)-coniine and (-)-Nmethylconiine are more potent than (+)-coniine and (+)-Nmethylconiine, respectively, in a mouse LD 50 toxicity model and in cell-based assays ( Table 2).…”
Section: Conium Alkaloidsmentioning
confidence: 99%
See 1 more Smart Citation
“…[50,60] Lethal doses (LD 50 ) in mice for selected alkaloids are presented in Table 2. [61] The differences in the chemical structures including stereochemistry impart differ-ences in toxicity/potency. For example, (-)-coniine and (-)-Nmethylconiine are more potent than (+)-coniine and (+)-Nmethylconiine, respectively, in a mouse LD 50 toxicity model and in cell-based assays ( Table 2).…”
Section: Conium Alkaloidsmentioning
confidence: 99%
“…In adult animals, poison hemlock alkaloids possess pharmacological actions similar to nicotine although the effects of hemlock alkaloids like coniine are longer lasting ,. Lethal doses (LD 50 ) in mice for selected alkaloids are presented in Table . The differences in the chemical structures including stereochemistry impart differences in toxicity/potency.…”
Section: Conium Alkaloidsmentioning
confidence: 99%
“…When compared to different alkaloids in nAChR of fetal rat muscle, the efficiency is, from the highest to the lowest: nicotine > coniine > tubocurarine > lobeline [ 118 ]. The toxicities of coniine enantiomers on human tumour cell line TE-671 expressing human foetal nAChR are, in order from the highest to the lowest: γ-coniceine > (−)-coniine > (−)- N -methylconiine > (±)-coniine > (±)- N -methylconiine > (+)-coniine > (+)- N -methylconiine [ 116 , 119 ]. The exact values for different coniine enantiomers are presented in Table 3 .…”
Section: Biological Activity Of Hemlock Alkaloidsmentioning
confidence: 99%
“…Coniine, γ‐coniceine, and N‐ methyl coniine are the principal alkaloids in Conium , with relative concentration depending on the stage of plant growth. All are toxic and teratogenic, and structural characteristics impart potency (γ‐coniceine > coniine > N‐ methyl coniine) (Leete and Olson, ; Keeler and Balls, ; Lee et al, ; Green et al, ). More detailed research on molecular bioactivity of these toxins is reported in a separate paper by Green et al () in this volume.…”
Section: Lupines Poison‐hemlock and Nicotiana Glaucamentioning
confidence: 99%